2007
DOI: 10.1103/physrevb.76.045414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deposition rate on morphology evolution of metal-on-insulator films grown by pulsed laser deposition

Abstract: The Harvard community has made this article openly available. Please share how this access benefits you. Your story matters where B is the kinetic rate constant for coalescence and f is the pulse frequency. Measurements of the percolation transition were consistent with this prediction. These findings indicate that the elementary processes included in the KMC simulation -substrate terrace diffusion, irreversible aggregation of hemispherical islands, and two-island coalescence, but neglecting the effects of Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
58
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 24 publications
10
58
0
Order By: Relevance
“…Currently, the most detailed atomistic * kostas.sarakinos@liu.se description of far-from-equilibrium 3D island formation is based on homoepitaxial systems in which 3D islands (mounds) form by deposition onto existing small islands, followed by atomic-step descent limited by the Ehlrich-Schwöbel barrier [15][16][17][18][19]. However, for weakly interacting film/substrate systems-including Ag/SiO 2 [20][21][22][23][24], Pd/TiO 2 [25], Cu/ZnO [26,27], and Dy/graphene [4,28]-3D islands develop before the initially formed one-atom-high islands are large enough to efficiently capture vapor-phase deposition flux. Moreover, 3D island formation is also known to occur in the absence of deposition flux due to surface restructuring via dewetting [29].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most detailed atomistic * kostas.sarakinos@liu.se description of far-from-equilibrium 3D island formation is based on homoepitaxial systems in which 3D islands (mounds) form by deposition onto existing small islands, followed by atomic-step descent limited by the Ehlrich-Schwöbel barrier [15][16][17][18][19]. However, for weakly interacting film/substrate systems-including Ag/SiO 2 [20][21][22][23][24], Pd/TiO 2 [25], Cu/ZnO [26,27], and Dy/graphene [4,28]-3D islands develop before the initially formed one-atom-high islands are large enough to efficiently capture vapor-phase deposition flux. Moreover, 3D island formation is also known to occur in the absence of deposition flux due to surface restructuring via dewetting [29].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Depending on the relative rates of island growth and coalescence, two morphological evolution regimes can be established in which merging islands can either fully relax into a compact shape and thereby complete coalescence (coalescence-controlled regime) or not (coalescence-free regime). [12][13][14][15][16] Analytical models and growth simulations [12,13,[17][18][19] have shown that in these two regimes the scaling laws under a continuous deposition flux read, [6,12,13] ≈ (1.75…”
mentioning
confidence: 99%
“…Warrender and Aziz's model [15,16] concerning the growth of metal-on-insulator thin films: at the beginning of the deposition thin films typically grow according to the Volmer-Weber mode, in which atoms grow in three-dimensional islands on the surface [17,18]. As the islands grow larger, they start to impinge each other driven by capillarity forces inducing the formation of clusters.…”
Section: -D) This Behaviour Is In Accordance Withmentioning
confidence: 99%